HORIZONTAL STRESS ORIENTATION FROM BOREHOLE BREAKOUT ANALYSIS IN WEST NATUNA BASIN, INDONESIA - Gumelar, Gumelar; Sapiie, Benyamin; Gunawan, Indra (Bulletin of Geology, 2023)
The West NatunaBasin is an intracontinental basin that characterized by number of Eocene –Oligocene half grabens, which inverted during Miocene time. West Natuna Basin formed under transtensional conditions, featuring half grabens trendingin a SW-NE direction, accompanied by sinistral (left-lateral) wrench zones striking NW-SE. The inversion reactivates mainly the border fault formed during rifting and resulted in the similar SW-NE structural trend. This research aims to investigate the stress orientation from boreholebreakout data that might be responsible for the structural formation in West Natuna area.Borehole breakout data in this research comprise into different types of data, image processed log from one well and caliper log (four arms and six arms) from eight vertical wells. The analysis performed differently for both of the data sets. The image processed log (FMI) data will give the indication of breakout and induced tensile clearly, while the breakout from caliper is interpreted based on some typical shape representing the borehole condition. The analysis from the borehole breakout will implies the minimum horizontal stress (Shmin) orientation that perpendicular to the maximum horizontal stress orientation (SHmax). The analysis resulted in a breakout trend N 36° to 79.5° with standard deviation 4.3-26.1°. The results of breakout analysis are comparable with the existing structure trend in southwestern part of West Natuna Basin that also showing similar trend SW-NE. Implied SHmaxorientation at NW-SE trend is coincidence with major strike slip fault that believed the main force for the inversion occurred in West Natuna Basin. As comparison, the regional main fault at neighborhood Malay Basin is relatively parallel withthe maximum horizontal stress (SHmax) orientation resulting the basin keep opened and subside until present day time. Key words: West Natuna Basin, borehole breakout, horizontal stress, inversion